2020
DOI: 10.1021/acssuschemeng.9b07434
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Nano-Structured Silicon from End-of-Life Photovoltaic Wafers with Value-Added Applications in Lithium-Ion Battery

Abstract: Millions of residential and industrial solar panels installed in the late 1980s and early 1990s are approaching the end of their life, resulting in the drastic accumulation of a potential source of environmental pollutiongiven the presence of hazardous materials, such as lead. The foreseen crisis, however, can be turned into a great opportunity by value-added recovery of precious solar-grade silicon (Si) to the highly desired nanostructured silicon for lithium-ion batteries (LIBs). Herein, we demonstrate a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 48 publications
(78 reference statements)
0
31
0
Order By: Relevance
“…This deleterious volume change stimulated the development of Si nanomaterials, because Si at the nano scale can withstand swelling without fracture during LiB cycling. This has been demonstrated for a variety of morphologies including Si nanoparticles (SiNP) [ 6 , 7 , 8 , 9 , 10 , 11 ], Si nanowires (SiNW) [ 3 , 12 , 13 , 14 ], Si nanotubes [ 15 , 16 ], and Si porous nanomaterials [ 17 , 18 , 19 ]. However, nanostructuration can be a costly process that needs to be carefully optimized for a dedicated application.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This deleterious volume change stimulated the development of Si nanomaterials, because Si at the nano scale can withstand swelling without fracture during LiB cycling. This has been demonstrated for a variety of morphologies including Si nanoparticles (SiNP) [ 6 , 7 , 8 , 9 , 10 , 11 ], Si nanowires (SiNW) [ 3 , 12 , 13 , 14 ], Si nanotubes [ 15 , 16 ], and Si porous nanomaterials [ 17 , 18 , 19 ]. However, nanostructuration can be a costly process that needs to be carefully optimized for a dedicated application.…”
Section: Introductionmentioning
confidence: 99%
“…A critical diameter was also predicted by a mechanical numerical model [ 23 ] at 90 nm for SiNPs and 70 nm for SiNWs. By contrast, several electrochemical studies in LiB investigated the impact of particle size on Si-based anode cycling for small [ 6 , 8 ] and large [ 7 , 8 , 9 ] SiNPs, with the best results at diameters of 20–50 nm. As for SiNWs, some studies have suggested the optimal diameter as being around 30 nm [ 10 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result obtained from our tests was a back-sheet specific surface density of 0.72 g/cm 3 .The mass of the back-sheet (assumed to remain constant throughout the EVA dissolution process) was subtracted from the mass obtained before and after the EVA dissolution to obtain the initial (mi) and final (mf) mass of the other PV sheet section constituents. The percentage detachment (δ) is given by Equation 1 as: δ = ((mimf) *100) / mi [1] Using the expression, percentage detachment was estimated and plotted. It can be seen from Figure 8 that toluene has a superior dissolution capability compared to hexane at ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The idea is to provide much needed material for the manufacture of new PV modules while addressing the matter of waste management and minimization. Recycling of end-of-life modules could also alleviate the energy burden associated with the fabrication of crystalline-silicon solar cells via the Siemens process (1) (8). The process is reported to be one of the most energy intensive stages in the production of silicon PV modules (9).…”
Section: Introductionmentioning
confidence: 99%